Capital utilization, market power, and the pricing of investment shocks - Garlappi, Lorenzo; Song, Zhongzhi (Journal of Financial Economics, 2017)
Capital utilization and market power crucially affect asset prices in an economy exposed to shocks that improve real investment opportunities through capital-embodied technological innovations. We embed these two mechanisms in a standard general equilibrium model and show that (i) the price of risk for investment shocks is negative under fixed capital utilization, but positive under sufficiently flexible capital utilization, and (ii) the equity return exposure to investment shocks is negative under perfect competition, but positive under high market power. We further show that, high market power, persistent components in technology growth, and a strong preference for early resolution of uncertainty are jointly important to quantitatively match the observed equity risk premium.